Detecção de defeitos em feixes tubulares de trocadores de calor por correntes parasitas assistida por simulação computacional - Côrte, Joaquim Smiderle (2019)
Eddy Current Test (ECT) has wide application in the service inspection of tubular bundles of shell and tube heat exchangers. However, due to the high sensitivity of the test to the various variables and their geometry, the analysis of signals in the tubesheet region becomes more complex. The presence of spurious and undesirable signals of large amplitudes in this region, generated simultaneously in the test, may overlap the signs of eventual discontinuities, making their detection difficult and / or impossible. The main objective of this work was to use the computational simulation of ECT as a tool to develop methodologies for a better signal evaluation. Using OPERA Cobham Software, virtual solids were constructed simulating the tubesheet region with geometric and dimensional characteristics similar to the real conditions. For greater reliability, the RHINOCEROS 3D software was used with the tomographic test and a new methodology was developed using the real defect geometry, in this case, chloride stress corrosion cracking (CSTCl). The results revealed a reliable diagnosis in the differentiation between the geometric signals and the discontinuity signals, even allowing to predict the probes detectability limits according to the size, orientation and vicinity of the discontinuities. Computer simulation with methodology developed from a real defect image proved to be applicable in the service damage test and showed to be a powerful tool for greater reliability of the ECT.